Quantification of Choriocapillaris with Optical Coherence Tomography Angiography: A Comparison Study - Chu, Zhongdi; Gregori, Giovanni; Rosenfeld, Philip J.; Wang, Ruikang K. (American journal of ophthalmology, 2019)
To demonstrate the variation in quantitative choriocapillaris (CC) metrics with various binarization approaches using optical coherence tomography angiography (OCTA). Retrospective, observational, cross-sectional case series. Macular OCTA scans, 3- × 3-mm and 6- × 6-mm, were obtained from normal eyes and from eyes with drusen secondary to age-related macular degeneration (AMD). The CC slab was extracted, and the CC flow deficits (FDs) were segmented with 2 previously published algorithms: the fuzzy C-means approach (FCM method) and Phansalkar's local thresholding (Phansalkar method). Four different values for the radius were used in order to investigate the effect on the FD segmentation when using the Phansalkar method. FD density (FDD), mean FD size (MFDS), FD number (FDN), FD area (FDA) and intercapillary distance (ICD) were calculated for comparison. Repeatability was assessed as coefficient of variation (CV), and Pearson's correlation analysis was conducted. Six eyes from 6 subjects with normal eyes and 6 eyes from 6 subjects with drusen secondary to AMD were scanned. The 3- × 3-mm scans resulted in higher repeatability than the 6- × 6-mm scans. For the Phansalkar method, larger values of the radius resulted in higher repeatability. ANOVA tests resulted in significant differences (P < 0.001) among the FCM method and the Phansalkar method with different radius options for all CC metrics and scan sizes investigated. In 3- × 3-mm scans, significant correlation was found between the FCM method and the Phansalkar method for all quantitative CC metrics other than FDN (all P < 0.001; 0.90 < r <0.99). Quantitative CC analysis with commercially available OCTA is complicated and researchers need to pay close attention to how they conduct such analyses.